Studying the effect of giving doses of different levels of the group of vitamins AD3E on some productive and doll traits For young male goats the local - Meitham K. Ali Al_Galiby; Huda Y. Shtib Al- khafaji (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted in the animal field of the College of Agriculture and Marshlands / University of Dhi Qar for the period from 6/12/2021 to 3/16/2022, and within that period the preparatory period was for 16 days (for adaptation), to study the effect of giving doses of different levels of the group of vitamins AD3E on some productive and doll traits For young male goats the local. The study included (12) animals between the ages of (3-4) months and their average weight (16.0-16.65) kg. Male Iraqi black goats were selected from local markets, purchased and all veterinary medical examinations were conducted for them, to ensure their safety and freedom from diseases, and the goats were divided. Randomly to (three treatments), each treatment included (four) animals for each treatment, which included the first treatment (control).T1 = 0 mL AD3E, left for comparison untreated with vitamins AD3E, T2 = 1 mL AD3E, and T3 = 2 mL AD3E, A concentrated diet of 3% of the live body weight was provided in the morning and in the evening, as the amounts of feed provided were adjusted depending on the progress of the new weight for each group. All treatments were fed on a ration containing crushed components, namely (crushed barley by 30%), (wheat bran by 26%), (corn). Yellow crushed 20%), (flour 20%), (urea 1%), (salts 3%) In addition to wheat straw provided as a -form side feed.The results were statistically analyzed using a complete random design, and the study concluded the following:It showed a significant increase in the weights of treatment T3 in weeks 6, 8, 10, 12 and recorded averages (23.75, 27.97, 32.75, 38.00) kg.The increase in weight showed a significant superiority of T3 in the amount of increase in total and daily weight with an average of (22) kg and (261) g / day, respectively.As for the efficiency of feed conversion, there was a significant decrease with the lowest average in favor of T3 treatment, which amounted to (3.90) kg feed / kg weight gain compared to the rest of the treatments.The results of the analysis showed a significant increase in the Packed Cell Volume( PCV) in the second and third months, and T3 treatment outperformed the rest of the treatments with an average of (48.75, 53.00)%, respectively.As for the hemoglobin concentration, the significant increase was for each of the T3 treatment and 33456the second and third months, with an average of (16.00, 17.25) g/cm3, respectively.The results of white blood cells showed a significant increase in the second and third months in favor of T3 treatment with an average of (8.84, 6.63) x/cm3 respectively.